Approximate Bayesian estimation for parameters of simple linear bivariate truncated t regression model - Elham Hussain; Haifa Saied (College of Education for Pure Sciences, 2020)
In this paper , It is obtained to approximate estimation for  parameters of the two-tailed truncated  regression model by Lindely approach . The prior  non- informative  was used for the regression parameters matrix when the variance matrix is ​​known and the two truncated points are also known. Under the quadratic loss function, the estimates approximations of the regression parameters matrix around zero up to third order moments are obtained.